Peran Baitul Maal Wa Tamwil dalam Pengembangan Ekonomi Syariah di Indonesia - Purwanto Purwanto; Muhammad Aliamza Annahl; Novio Dyfa Pratama; Ismail Ismail (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
Baitul Maal wa Tamwil (BMT) is an Islamic Microfinance Institution that has two main functions, namely as collectors, distributors, utilization of zakat funds, infaq, alms, waqf and can function as productive economic empowerment that provides financial services using sharia principles. . Its presence in the community has a significant impact on the Indonesian economy, especially in the field of microeconomics. This research was made using a qualitative descriptive method to analyze, summarize, and describe its role in the development of Islamic economics. Through SWOT analysis and interviews with respondents on mudarabah financing, it is shown that BMT has an important role in increasing micro-enterprises and improving economic development in Indonesia, although it still has several weaknesses. This institution encourages the economic growth of the community through financing to micro-enterprises that need funds for their business capital.